Post-secular Anthropology as Recognition and the Limits of Understanding: Responding to Experiences of Jinn Possession in Morocco. - Rasanayagam, Johan (Social Analysis, 2023)
This article contributes to discussions around a post-secular anthropology that seek to engage seriously with religious traditions and theology. Conversations in Morocco with Muslims who experienced possession by jinn spirits point to the importance of recognition. To understand those experiences risks translating them into my concepts. Recognizing them accepts that what the other says has significance. They call me to visit the broader Islamic tradition that they creatively draw on in an effort to decenter my own thinking and to open up to possibility. This space for possibility and the limits of understanding are explored by putting into dialogue Maurice Merleau-Ponty's phenomenology as critique of Descartes's dualism of mind and world, with a discussion in the Islamic tradition, between al-Ghazālī and Ibn Sīnā.